Writing new worlds: the cultural dynamics of curiosity in early modern Europe - Lopes, Marília dos Santos (2019)
Writing New Worlds analyses the different ways in which travel literature constituted a fundamental pillar in the production of knowledge in the modern era. The impressive frequency of publication and the widespread circulation of translations and editions account for the leading and essential contribution of travel literature for a better understanding and awareness about the dynamics and practices associated with decoding and making sense of the prose of the world. These texts, in some cases accompanied by illustrations, covered a broad and extensive panoply of languages, grammars and ways of seeing, translating and writing new worlds. In drawing special attention to internationally less-studied sources from Portugal and Germany, the book shows how authors, scholars and artists between the 15th and 17th centuries responded to the challenges of modernity, and explores the cultural dynamics involved in grasping and understanding the New.